Evaluation of historic, current and future water demand in the Olifants River Catchment, South Africa - McCartney, Matthew P.; Arranz, Roberto (International Water Management Institute, 2007)
Water resource development has played a significant role in the expansion of agriculture and industry in the Olifants River Catchment. However, currently water deficit is one of the major constraints hampering development in the catchment; both the mining and agricultural sectors are producing below optimal levels because of their reliance on insufficient supplies. In this study, the Water Evaluation and Planning (WEAP) model was used to evaluate scenarios of historic, current and future water demand in the catchment. For each scenario, the WEAP model was used to simulate demand in five different sectors (rural, urban, mining, commercial forestry and irrigation) over a 70-year period of varying rainfall and hydrology. Levels of assured supply were estimated for each sector and the economic cost of failing to provide water was predicted. For the future scenarios, the impact of infrastructure development and water conservation measures were assessed. The study illustrates how a relatively simple model can provide useful insight for resource planning and management.